Visualizing transport in thiazole flanked isoindigo-based donor–acceptor polymer field-effect transistors. Issue 39 (16th September 2022) - Barron, John; Attar, Salahuddin; Bhattacharya, Payal; Yu, Ping; Al-Hashimi, Mohammed; Guha, Suchismita
Abstract : Replacing S with Se in fluorinated isoindigo (IID) copolymers enhances charge transport properties in field-effect transistors (FET). Nonlinear optical imaging from IID FETs helps visualize transport. Abstract : Fluorination of donor–acceptor copolymers has been one strategy towards enhancing polymer coplanarity, increasing crystallinity, and improving charge transport mechanisms in organic devices. Herein, we report on the synthesis of thiazole flanked fluorinated isoindigo (IID) copolymers and demonstrate their field-effect transistor (FET) properties. The selenophene-substituted IID shows improved performance over the thiophene units. Different FET geometries were fabricated and tested. Top-gate FETs with varying dielectric layers showed n-type transport with electron carrier mobilities of the order of 10 −2 cm 2 V −1 s −1 and on/off ratio of 10 5 . Along with improving the electronic properties, fluorination is an effective means of enhancing the nonlinear optical properties. We exploit this feature by observing the semiconductor-dielectric polarization induced by the applied electric field and the injected carriers. Time-resolved electric field-induced second harmonic generation method is used to visualize the carrier motion within the FET channel region, which gives an alternate estimate of the electron carrier mobility, free from contact resistance issues.